2019
DOI: 10.3390/pharmaceutics11070300
|View full text |Cite
|
Sign up to set email alerts
|

Latest Advances in the Development of Eukaryotic Vaults as Targeted Drug Delivery Systems

Abstract: The use of smart drug delivery systems (DDSs) is one of the most promising approaches to overcome some of the drawbacks of drug-based therapies, such as improper biodistribution and lack of specific targeting. Some of the most attractive candidates as DDSs are naturally occurring, self-assembling protein nanoparticles, such as viruses, virus-like particles, ferritin cages, bacterial microcompartments, or eukaryotic vaults. Vaults are large ribonucleoprotein nanoparticles present in almost all eukaryotic cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 75 publications
0
27
0
Order By: Relevance
“…Vaults are ribonucleoprotein complexes widely associated with the induction of chemoresistance and long-term chemotherapy failure [ 126 ] and for which expression plays a role in preventing apoptosis and regulating autophagy [ 127 , 128 , 129 , 130 ]. Vault complexes are composed primarily of three proteins: a 100-kDa major vault protein (MVP), a 290-kDa telomerase-associated protein 1 (TEP1), and a 193-kDa vault poly (ADP-ribose) polymerase (VPARP) complexed with noncoding vault RNA (vtRNAs) [ 126 ].…”
Section: Known Roles For Nsun2 In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Vaults are ribonucleoprotein complexes widely associated with the induction of chemoresistance and long-term chemotherapy failure [ 126 ] and for which expression plays a role in preventing apoptosis and regulating autophagy [ 127 , 128 , 129 , 130 ]. Vault complexes are composed primarily of three proteins: a 100-kDa major vault protein (MVP), a 290-kDa telomerase-associated protein 1 (TEP1), and a 193-kDa vault poly (ADP-ribose) polymerase (VPARP) complexed with noncoding vault RNA (vtRNAs) [ 126 ].…”
Section: Known Roles For Nsun2 In Cancermentioning
confidence: 99%
“…Vaults are ribonucleoprotein complexes widely associated with the induction of chemoresistance and long-term chemotherapy failure [ 126 ] and for which expression plays a role in preventing apoptosis and regulating autophagy [ 127 , 128 , 129 , 130 ]. Vault complexes are composed primarily of three proteins: a 100-kDa major vault protein (MVP), a 290-kDa telomerase-associated protein 1 (TEP1), and a 193-kDa vault poly (ADP-ribose) polymerase (VPARP) complexed with noncoding vault RNA (vtRNAs) [ 126 ]. vtRNAs have been shown to have the ability to recognize chemotherapeutic compounds, such as mitoxantrone, and it has been suggested that the binding of vtRNAs to these chemotherapeutic compounds prevents the drugs from reaching their target sites and consequently in cancer chemoresistance [ 131 , 132 ].…”
Section: Known Roles For Nsun2 In Cancermentioning
confidence: 99%
“…Almost all known vaults consist of one major protein component known as the major vault protein (MVP), with minor components including poly(ADP-ribose) polymerase (VPARP), telomerase and small non-translated RNA. 83 Structural and biophysical studies have shown that MVP and VPARP interact through involvement of a particular domain known as interaction domain (INT) present on VPARP. The domain consists of 161 amino acids and resides on the C-terminus of VPARP.…”
Section: Vaultmentioning
confidence: 99%
“…84 Because of its unique architecture and its large cavity size, the vault cage has been widely used for cargo encapsulation of numerous molecules including therapeutics, small molecules and polymers. 83,85 Recently it was used to load MnP for bioremediation. The enzyme was packaged inside vault by genetically fusing it with INT-domain, and then encapsulation was achieved via high affinity interaction between the INT domain and vault interior.…”
Section: Vaultmentioning
confidence: 99%
“…Biological protein-based nanoparticles are advantageous in having biodegradability, bioavailability, and relatively low cost. Many protein nanoparticles, for instance naturally occurring protein cages such as ferritin, are easy to process and can be modified to achieve desired specifications such as size, morphology, and weight [9,10,11]. Natural product-based nanomedicine include, among the most common types of nanoparticles, polymeric micelles, solid lipid nanoparticles, liposomes, inorganic nanoparticles and dendrimers [3,12].…”
Section: Introductionmentioning
confidence: 99%